Energy Adequacy During Suhoor and Glycemic Stability for Elderly Diabetics - Achdi Kurnia; Hafidz Muhammad Prodjokusumo; Rahmat Dahlan (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Fasting is a mandatory worship practice for Muslims, including for the elderly with type 2 diabetes mellitus (DM2). However, this condition poses challenges in maintaining glycemic stability and energy adequacy from suhoor to iftar time. The study identified optimal nutritional strategies to achieve energy sufficiency during suhoor and to maintain stable blood glucose levels in the elderly with DM2. The research uses the Systematic Literature Review (SLR) approach, examining scientific articles indexed in Scopus and Web of Science from 2010–2024. Literature selection is carried out through the stages of identification, screening, and eligibility using the PRISMA guidelines. The results of the study showed that a balanced composition of suhoor food including complex carbohydrates (100–150 g), animal protein (50–75 g), vegetable protein (±50 g), fibrous vegetables (±100 g), low glycemic index fruit (±100 g), healthy fats (30–50 g), low-fat milk (±200 ml), and adequate hydration (2–3 glasses of water) play an important role in maintaining glycemic stability in the elderly with DM2. The energy needs of the elderly with diabetes range from 25–30 kcal/kg of body weight per day, with suhoor contributing around 30–40% of the total daily energy needs (±450–600 kcal). Energy intake below the sufficiency threshold can increase the risk of hypoglycemia, fatigue, and impaired metabolic function. In contrast, energy intake above the maximum limit can lead to hyperglycemia, obesity, and insulin resistance. The importance of planning a balanced suhoor menu to maintain stable blood glucose levels in elderly individuals with DM2 during fasting.